Cost of Financial Distress and Firm Performance - Widarwati, Estu; Sartika, Dewi (UI Scholars Hub, 2018)
The business performance become an important thing to be main goal of firm activities to get the competitive advantage, but it is contrary with the recession may bring a probability of firm’s decreasing and liquidation. The uncertainty of global economy provides the importance in developing model to monitor, identify and asses potential risks which can threat business sustainability. Cost of Financial Distress (CFD) is one of tools for identifying firm performance decline early risk such as sales growth and stock return, so it can reduce the loss possibility before all lead to bankruptcy. This research aims to explain the evidence of CFD in Indonesia by using opportunity loss and consequency to firm performance. The datas used are 231 firms of Indonesia Stock Exchange (IDX) in 2011 – 2015 and panel regression used for presenting the impact of CFD to firm performance. Consistency of the theory that cost tend to increase following cash flow realization which may be lower in uncertainty of economiy. The analysis finds that Indonesia’s industry have higher CFD and low sales growth after based year of uncertainty economy. The regression result also finds CFD have negative impact to firm’s sales growth. The result propose that CFD can be used as an early detection tool for reducing loss possibility of firm’s market share.